Book Review: E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35 - Cone, L. Winston (Journal of Asian and African Studies, 1975)
"E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35" published on 01 Jan 1975 by Brill.
Keywords: book.review; dept.his